Instrumental selection of tooth color in prosthodontic rehabilitation - Đurišić Slobodan; Milić-Lemić Aleksandra; Obradović-Đuričić Kosovka; Popović Olga (Serbian Medical Society - Dental Section, Belgrade, 2007)
Tooth color selection in prosthodontics is a very important factor for successful rehabilitation. The aim of this paper was to present different instruments for tooth color selection in prosthodontic rehabilitation. Knowledge of basic principles of a complex psychophysical phenomenon such as color is of essential interest in prosthodontic therapy. Furthemore, the mechanism of physiological perception of color and available methods for an objective determination of tooth color are also presented in the paper.